Progressivity and non-compliance in the interactions between children with autism and their parents - Chen, Rachel Siew Yoong. (2013)
Autism has been the subject of many studies, but there is still much uncertainty about the communicative abilities of individuals with autism. Many studies question their very possession of “communicative intent”. Following Sterponi (2010), this paper examines the spontaneous everyday interactions between two boys with autism and their parents, and the nature of intersubjectivity that underlies their interactions. It shows that the verbal and non-verbal behaviour of such children, which might ordinarily have been dismissed or deemed as idiosyncratic, often plays an essential role in contributing to a sequence. While there is an intrinsic presence of intersubjectivity in any interaction, there are moments when tension between mutual understanding and sequence progressivity ensues from an interactional sequence. The analysis examines such cases, where the child risks a breakdown of intersubjectivity with noncompliance, and yet continues to retain the progressivity of the sequence. In many of these instances, their noncompliance also results in a more favourable sequence outcome for them. The study suggests that individuals with autism may have a degree of competence in progressing sequences in interaction.